Effect of post-slaughter time and storage conditions on chemical and microbial changes in locally marketed beef (Bangladesh Journal of Animal Science, 2015)
Fresh meat is commonly marketing at environmental temperature for long time in many developing countries including Bangladesh. The present study was conducted to assess whether elapsed time between slaughter and preservation and storage conditions influence the chemical and microbial changes of locally marketed beef. Meat samples were collected from local markets and divided into two groups, morning and evening beef. Morning beef was collected immediately after slaughtering from healthy cattle while evening one was collected 8 h after slaughtering. The samples were kept either in refrigerator (4oC) or freezer (-20oC). Refrigerated samples were stored for 7 days and analyzed on day1st, 3rd and 7th while frozen samples were stored for 90 days and analyzed on day 3rd, 45th and 90th. Results showed that there was a significant difference in chemical and microbial parameters between morning and evening beef (p